Graded origami honeycomb for energy absorption - de Waal, L (2022)
This thesis is concerned with the design of new cellular structures whose properties can be easily tuned to optimise the management of both quasi-static and dynamic external loads. This was achieved through the application of origami techniques, which allowed the mechanical performance to be functionally graded through the adjustment of the underlying crease pattern. The body of work is segmented into four areas of focus: